Theoretical Investigation Of The Insulator-Metal Transition Point Of Nickel Monoxide - Osarodion Ebomwonyi; John O. A. Idiodi (European Scientific Journal, ESJ, 2016)
The study of the effects of applying high pressure by compression on materials is fundamental to a range of problems in condensed matter physics, materials science, technology, etc. Transition of an insulator into a metallic state is in general a basic phenomenon related to a wide range of physical systems. Nickel monoxide has been studied at different volume compression ratios by employing optical spectra and electronic structure calculations using the density functional theory implemented in the MindLab 5 code that made use of the local density approximation plus the Hubbard on-site Coulomb interaction parameter. Insulator-metal transition point was recorded at 0.60 volume compression ratio from both calculations and a transition pressure of 271 GPa was obtained using the Murnaghan equation of state.